High-wet-strength nano silk paper

By using hemp or straw fibers as the substrate layer in traditional paper, combined with polymer coating and colloidal base layer, the problem of insufficient performance of traditional paper in humid environments is solved, and the research and development of high-humidity and strength nano silk paper is achieved, meeting the demand for high-performance paper in many fields, and promoting the sustainable development of paper production.

CN119663671APending Publication Date: 2025-03-21DONGGUAN JINGPENG PAPER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510078062.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Traditional paper lacks performance in humid environments, making it difficult to meet the needs of packaging materials and preservation of calligraphy and painting works used in humid environments.

Method used

High-wet strength nano silk paper is used, which consists of hemp fiber or straw fiber as the substrate layer, combined with polymer coating and colloidal substrate layer, and improves the wet strength and multifunctional performance of the paper through fiber pretreatment technology.

Benefits of technology

It significantly improves the wet mechanical strength, waterproofness, wear resistance and adhesive stability of paper, meets the demand for high-performance paper in different fields, and achieves the sustainable development of paper production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663671A_ABST
    Figure CN119663671A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of silk paper, and particularly relates to high-wet-strength nano silk paper which comprises a base material layer, and the base material layer is a basic network structure of the paper formed by interweaving hemp fibers or straw fibers and plant fibers; a polymer coating is coated on the base material layer, and a colloid substrate layer is arranged at the bottom of the base material layer. The base material layer is a tough network formed by interweaving hemp or straw fibers, so that the strength and the stability are improved, and the environment-friendly effect is achieved. The thickness of the polymer coating can be adjusted, and the waterproof and breathable performance can be optimized according to scenes. And the colloid substrate layer has multiple selections and is wide in viscidity adaptation. The fiber pretreatment technology improves the uniformity and strength of the paper, and the whole paper has excellent performance in multiple fields and wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of silk paper, in particular to high-wet-strength nano silk paper. Background Art

[0002] Traditional paper is usually made of plant fibers. Although it has certain strength and flexibility, it easily loses its strength in a humid environment and becomes brittle and easy to break. This limits the application of paper in some specific fields, such as packaging materials that need to come into contact with water, and the preservation of calligraphy and painting works in a humid environment.

[0003] With the continuous development of science and technology and the growing needs of various industries, the demand for paper with high wet strength performance is becoming increasingly urgent. In the field of culture and art, calligraphy and painting works require better backing paper to protect their integrity in different environments; in the packaging field, especially for food, medicine and other products with high moisture-proof requirements, paper is required to effectively block moisture while maintaining a certain strength and stability.

[0004] The development of nanotechnology has provided a new way to improve the performance of materials. Introducing nanoscale materials into paper can improve the performance of paper. Silk, as a natural polymer fibrous protein, has good mechanical properties, biocompatibility and degradability. Nanosilk extracted from silk can be combined with plant fibers of paper to significantly improve the dry and wet mechanical strength of paper, while increasing the hydrophobicity, gas barrier and printability of paper.

[0005] As renewable resources, hemp fiber and straw fiber have the advantages of wide sources and low cost. Using them as the substrate layer of high wet strength nano silk paper can reduce the production cost of paper and achieve effective utilization of resources. However, hemp fiber and straw fiber contain more lignin and hemicellulose, and need to be properly pretreated to improve the performance of paper.

[0006] In summary, the research and development of high wet-strength nano-silk paper aims to solve the problem of insufficient performance of traditional paper in a humid environment, combining the advantages of nanotechnology and natural materials to meet the needs of different fields for high-performance paper. At the same time, renewable resources such as hemp fiber and straw fiber are used to achieve sustainable development of paper production. Summary of the invention

[0007] 1. Technical issues to be resolved

[0008] In view of the shortcomings of the prior art, the present invention provides a high-wet-strength nano-silk paper, which solves the problems raised in the above-mentioned background technology.

[0009] (II) Technical solution

[0010] In order to achieve the above-mentioned purpose, the present invention specifically adopts the following technical solutions:

[0011] A high wet strength nano silk paper comprises a substrate layer, wherein the substrate layer is hemp fiber or straw fiber, and the plant fibers are interwoven to form a basic network structure of the paper;

[0012] A polymer coating is coated on the substrate layer, and a colloid base layer is arranged at the bottom of the substrate layer.

[0013] Further, the polymer coating is a polyvinyl alcohol coating or a polyvinyl alcohol coating.

[0014] Furthermore, the colloid base layer is gum arabic, gelatin or polyvinyl butyral.

[0015] Furthermore, the thickness of the polymer coating can be adjusted within a certain range to meet the requirements of different application scenarios for paper performance, and the coating thickness ranges from 0.1 mm to 1 mm.

[0016] A method for manufacturing high wet-strength nano-silk paper comprises the following steps:

[0017] S1, performing fiber pretreatment on the substrate layer;

[0018] S2, preparing a polymer coating solution;

[0019] According to the selected polymer coating type, a corresponding coating solution is prepared;

[0020] If it is a polyvinyl alcohol coating, add polyvinyl alcohol powder to an appropriate amount of water, heat it to 80℃-90℃ and stir it to completely dissolve it to form a polyvinyl alcohol solution with a mass concentration of 5%-15%. Some additives such as dispersants and defoamers can be added as needed to improve the stability of the solution and the coating performance;

[0021] In the case of a polydopamine coating, dopamine hydrochloride is dissolved in a buffer solution, such as tris(hydroxymethyl)aminomethane hydrochloride buffer, at a concentration of 1 g / L to 3 g / L, and then a certain amount of an oxidant, such as ammonium persulfate, is added under stirring to initiate a self-polymerization reaction of dopamine to form a polydopamine solution;

[0022] S3, applying a polymer coating;

[0023] Laying the pretreated substrate layer flat on a coating device, and uniformly coating the polymer coating solution on the substrate layer using a suitable coating method;

[0024] The doctor blade coating method can be used to control the coating thickness between 0.1 mm and 1 mm by adjusting the gap and pressure of the doctor blade;

[0025] You can also use the roller coating method, select a suitable coating roller, control the speed and pressure of the roller, and ensure that the coating is uniform and the thickness meets the requirements;

[0026] S4, drying the polymer coating;

[0027] The paper coated with the polymer coating is placed in a drying device for drying to remove moisture from the coating;

[0028] For the polyvinyl alcohol coating, it can be dried at a temperature of 50°C-70°C for 2-4 hours to allow the polyvinyl alcohol to fully form a film;

[0029] For the polydopamine coating, the coating can be dried at room temperature for 12-24 hours to allow the polydopamine coating to stably adhere to the substrate layer;

[0030] S5, preparing a colloid base solution;

[0031] Prepare the appropriate solution based on the type of glial substrate selected;

[0032] If it is gum arabic, add gum arabic powder to an appropriate amount of water, heat to 50°C-60°C and stir to dissolve it to form a solution with a mass concentration of 10%-20%;

[0033] If it is gelatin, soak the gelatin particles in warm water for a period of time and then heat to 40℃-50℃ to completely dissolve them to form a solution with a mass concentration of 8%-15%;

[0034] For polyvinyl butyral, dissolve it in an organic solvent, such as ethanol, to form a solution with a mass concentration of 15%-25%;

[0035] S6, coating the colloid base;

[0036] The prepared colloid base solution is evenly coated on the bottom of the substrate layer.

[0037] The spraying method can be used to ensure that the base solution is evenly covered on the bottom of the substrate layer, and the thickness can be controlled between 0.05 mm and 0.5 mm;

[0038] S7, drying and curing;

[0039] The paper coated with the colloid substrate is placed in the drying equipment again for drying and curing;

[0040] For gum arabic and gelatin bases, dry at 40℃-50℃ for 3-5 hours to fully solidify;

[0041] For the polyvinyl butyral substrate, it can be dried at 60°C-80°C for 2-3 hours to volatilize the organic solvent and solidify the substrate.

[0042] Furthermore, the hemp fiber contains more lignin and hemicellulose. For flax fiber, lignin degrading enzymes, such as laccase and xylanase, are used to decompose lignin and hemicellulose. Laccase can oxidize phenolic hydroxyl groups in lignin to make the lignin structure loose, while xylanase can hydrolyze xylan in hemicellulose. At a temperature of 40-50°C and a pH of 4.5-5.5, the hemp fiber is immersed in an enzyme-containing buffer solution for 4-6 hours, which can effectively remove part of the lignin and hemicellulose without damaging the strength of cellulose. When the hemp fiber is made into paper, it can be better dispersed, thereby improving the uniformity and strength of the paper.

[0043] Furthermore, the main components of the straw fiber are cellulose, hemicellulose and lignin. For the straw fiber, dilute sulfuric acid treatment can be used. The straw fiber is immersed in a sulfuric acid solution with a mass fraction of 1-3%, and treated at 60-70°C for 2-3 hours. Sulfuric acid can hydrolyze the glycosidic bonds in the hemicellulose and partially dissolve the hemicellulose. At the same time, it can also cause a certain degree of degradation of lignin, thereby making the fiber better dispersed. However, it is necessary to control the acid concentration and treatment time to avoid excessive degradation of cellulose.

[0044] (III) Beneficial effects

[0045] Compared with the prior art, the present invention provides a high wet-strength nano-silk paper, which has the following beneficial effects:

[0046] In the present invention, the substrate layer adopts hemp fiber or straw fiber, which combines the high strength and toughness of hemp with the wide source, low cost and degradability of straw to construct a stable and elastic network structure, greatly improving the initial strength and dimensional stability of paper, far exceeding traditional paper, and providing support for sustainable development and high performance requirements. The polymer coating adopts polyvinyl alcohol, which has excellent film-forming property, flexibility and hydrophilicity, and can accurately adjust the thickness according to needs. Thick coating improves waterproof and wear resistance and is suitable for packaging, and thin coating maintains air permeability and flexibility to match the backing paper for calligraphy and painting. The limitations of traditional coatings are broken through in multiple dimensions to achieve a leap in the surface performance of paper. The colloid base layer introduces a multi-system of gum arabic, gelatin or polyvinyl butyral, which can accurately adapt the viscosity according to different scenarios, and show its strengths in many fields such as food labels, medical packaging, outdoor advertising, etc., breaking the limitations of traditional colloid base layers, ensuring that the paper is firmly pasted and the function is reliable. In addition, the unique fiber pretreatment technology effectively optimizes the performance of hemp and straw fibers, comprehensively improves the starting point of paper quality, and shows excellent application potential in many fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 It is a schematic diagram of the structure of the present invention;

[0048] Figure 2 Schematic diagram of the structure of the substrate layer of the present invention;

[0049] Figure 3 The present invention is a flow chart of the manufacturing method.

[0050] In the figure: 1, substrate layer; 2, polymer coating; 3, gelatinous base layer. DETAILED DESCRIPTION

[0051] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0052] Example

[0053] like Figure 1-2 As shown, a high wet-strength nano-silk paper proposed in one embodiment of the present invention comprises a substrate layer 1, wherein the substrate layer 1 is hemp fiber or straw fiber, and the plant fibers are interwoven to form a basic network structure of the paper;

[0054] A polymer coating layer 2 is coated on the substrate layer 1, and a gelatin base layer 3 is provided at the bottom of the substrate layer 1;

[0055] The substrate layer 1 is made of hemp fiber or straw fiber, and the plant fibers are interwoven to form the basic network structure of the paper. Hemp fiber has the characteristics of high strength and good toughness, and straw fiber is widely available, low-cost and degradable. The mixed interweaving of the two gives the paper good initial strength and environmental protection characteristics, lays the foundation for the overall performance of the paper, provides a supporting framework, determines the basic mechanical properties and dimensional stability of the paper, and is the key structure for carrying other functional layers.

[0056] The polymer coating 2 is a polyvinyl alcohol coating or a polyvinyl alcohol coating, and the thickness can be adjusted in the range of 0.1 mm to 1 mm. Polyvinyl alcohol has good film-forming properties, flexibility and hydrophilicity, and can improve the surface properties of paper. Adjusting the thickness can adapt to different scenarios, such as thicker coatings to enhance waterproof and wear resistance for packaging; thin coatings maintain the air permeability and flexibility of paper, meet the needs of calligraphy and painting backing paper, improve the surface quality of paper, and enhance protection and functional adaptability.

[0057] The colloid base layer 3 is made of gum arabic, gelatin or polyvinyl butyral. Gum arabic and gelatin are natural, environmentally friendly, moderately sticky and have good biocompatibility, while polyvinyl butyral has strong stickiness and good water resistance. This layer provides stickiness to the bottom of the paper, ensures good adhesion to the contact surface, prevents the paper from sliding and shifting during use, maintains structural integrity, and selects different gums to adjust the stickiness according to the use environment, thereby expanding the application range of the paper.

[0058] In high-wet-strength nano-silk paper, the hemp fibers or straw fibers of the substrate layer 1 are interwoven into a tight network structure to build a stable support framework, giving the paper basic strength and morphological stability. Its fiber characteristics determine the basic performance trend of the paper and lay the foundation for the subsequent functional realization. The polymer coating 2 forms a continuous protective film with the characteristics of polyvinyl alcohol, and optimizes protection and functional adaptation through thickness adjustment. The thick coating enhances waterproofness and wear resistance, and relies on its own barrier and film-forming properties to block water and resist friction in the packaging field; the thin coating maintains air permeability and flexibility, meets the needs of calligraphy and painting backing paper, and achieves performance balance through precise adjustment. The colloid base layer 3 uses the viscosity of gum arabic, gelatin or polyvinyl butyral to strongly adhere to the contact surface, stabilize the paper structure from the bottom, and prevent the paper from shifting and loosening through the action of the colloid properties and the intermolecular force of the contact material, ensuring the integrity of the structure during use. Different colloids adjust the viscosity according to the environment, and optimize the pasting effect on demand in scenes such as labels and decorative paper. The synergistic effect of various structures makes the paper excellent in performance and reliable in functions in multiple fields.

[0059] As shown in 1, in some embodiments, the polymer coating 2 is a polyvinyl alcohol coating or a polyvinyl alcohol coating; the polymer coating 2 is selected from a polyvinyl alcohol coating, which has significant advantages. Polyvinyl alcohol has excellent film-forming properties and can evenly cover the surface of the substrate layer 1 to form a continuous and dense protective film. This property effectively improves the smoothness of the paper surface, reduces the roughness and porosity of the paper surface, reduces the permeability of the paper to liquids and gases, and enhances the waterproofness and barrier properties of the paper.

[0060] Its good flexibility gives the paper better foldability and bending resistance. During multiple folding or bending processes, the coating can deform with the paper without breaking or falling off, allowing the paper to maintain structural integrity and stable performance in scenarios that require frequent bending, such as packaging and bookmaking.

[0061] Furthermore, polyvinyl alcohol molecular chains contain a large number of hydroxyl groups, which are hydrophilic and have a certain water retention capacity, playing a key role in specific application scenarios. For paper applications that require a certain amount of moisture control, such as humidity-sensitive product packaging or artistic creation paper, it can accurately adjust the moisture content of the paper to prevent the paper from being overly dry and brittle or damp and soft, ensuring product quality and artistic expression.

[0062] like Figure 1As shown, in some embodiments, the gelatinous base layer 3 is gum arabic, gelatin or polyvinyl butyral; the gum arabic, gelatin or polyvinyl butyral selected for the gelatinous base layer 3 each has unique properties and functions. Gum arabic, as a natural plant gum, is mainly composed of polysaccharides, has excellent viscosity and good solubility, and can form a firm and stable adhesion layer at the bottom of the paper. In some application scenarios that have moderate viscosity requirements and focus on environmental protection and natural material properties, such as food label paper or handmade art paper, gum arabic can make the paper fit tightly to the target surface, avoiding the displacement or falling off of the paper during transportation and display. At the same time, due to its natural origin, it is suitable for use in environments with strict environmental requirements.

[0063] Gelatin is derived from the hydrolyzate of animal collagen, with excellent biocompatibility, strong viscosity and good film-forming properties. In medical packaging paper or biological test strips, where biological safety requirements are extremely high, the gelatin base can ensure that the paper is firmly combined with biological samples or medical products to prevent sample contamination or product damage due to accidental peeling. It can form a stable colloidal system in aqueous solution, and after drying, it forms a tough, transparent film, which provides reliable structural support and viscosity guarantee for the paper base, helping to maintain the overall physical integrity and functional stability of the paper.

[0064] Polyvinyl butyral is a synthetic polymer adhesive with excellent water resistance, chemical resistance and high transparency. In applications such as outdoor advertising paper, waterproof labels or industrial packaging paper in humid environments, its strong water resistance can effectively resist rain and moisture erosion, ensuring that the paper maintains adhesion and structural stability under harsh humidity conditions for a long time. Its chemical stability enables it to withstand contact with a variety of chemical substances without deterioration or loss of viscosity, broadening the application scope of paper in the fields of chemical product packaging, special environment labeling, etc., and providing paper with long-lasting and reliable bottom adhesion and protective performance guarantees.

[0065] like Figure 1 As shown, in some embodiments, the thickness of the polymer coating 2 can be adjusted within a certain range to meet the requirements of different application scenarios for paper performance, and the coating thickness ranges from 0.1 mm to 1 mm; the thickness of the polymer coating 2 can be flexibly adjusted within the range of 0.1 mm to 1 mm, laying a solid foundation for the precise adaptation of high-wet-strength nano-silk paper to diversified application scenarios. When paper is used in packaging fields such as food and electronic devices that have strict moisture-proof requirements, the coating thickness is appropriately increased to close to 1 mm. With the density and barrier properties of the polyvinyl alcohol coating, a strong moisture-proof barrier can be constructed, which greatly reduces the rate at which external moisture penetrates into the paper, effectively avoiding the risk of product quality deterioration due to moisture, and effectively extending the product storage cycle and shelf life.

[0066] In the cultural and artistic fields such as calligraphy and painting creation and ancient book restoration, the coating thickness tends to be adjusted to about 0.1 mm. This thickness can optimize the flatness and fineness of the paper surface through the coating, providing a high-quality carrier for the smudges of calligraphy and painting, the outlines of lines, and the presentation of text patterns in ancient books, and can also maximize the air permeability and flexibility of the paper itself. It ensures that during long-term storage and frequent reading and viewing, the paper will not mold due to internal water vapor accumulation or be damaged due to rigid texture, thus protecting the inheritance of cultural and artistic treasures.

[0067] In conventional application scenarios such as labels and decorative wallpapers, the coating thickness can be accurately selected in the range of 0.1 mm to 1 mm according to the specific use environment and functional requirements. For example, the thickness of decorative wallpapers used indoors for a short period of time can be appropriately reduced to balance decorativeness and economy; the thickness of labels and stickers posted outdoors for a long time can be appropriately increased to improve weather resistance and adhesion firmness, so that the paper can perform ideally in multiple scenarios and expand the breadth and depth of application.

[0068] A method for manufacturing high wet-strength nano-silk paper comprises the following steps:

[0069] S1, performing fiber pretreatment on the substrate layer (1);

[0070] S2, preparing a polymer coating (2) solution;

[0071] According to the type of the selected polymer coating (2), prepare a corresponding coating solution;

[0072] If it is a polyvinyl alcohol coating, add polyvinyl alcohol powder to an appropriate amount of water, heat it to 80℃-90℃ and stir it to completely dissolve it to form a polyvinyl alcohol solution with a mass concentration of 5%-15%. Some additives such as dispersants and defoamers can be added as needed to improve the stability of the solution and the coating performance;

[0073] In the case of a polydopamine coating, dopamine hydrochloride is dissolved in a buffer solution, such as tris(hydroxymethyl)aminomethane hydrochloride buffer, at a concentration of 1 g / L to 3 g / L, and then a certain amount of an oxidant, such as ammonium persulfate, is added under stirring to initiate a self-polymerization reaction of dopamine to form a polydopamine solution;

[0074] S3, applying a polymer coating (2);

[0075] Laying the pretreated substrate layer (1) flat on a coating device, and uniformly coating the polymer coating solution on the substrate layer (1) using a suitable coating method;

[0076] The doctor blade coating method can be used to control the coating thickness between 0.1 mm and 1 mm by adjusting the gap and pressure of the doctor blade;

[0077] You can also use the roller coating method, select a suitable coating roller, control the speed and pressure of the roller, and ensure that the coating is uniform and the thickness meets the requirements;

[0078] S4, drying the polymer coating (2);

[0079] placing the paper coated with the polymer coating (2) into a drying device for drying to remove moisture from the coating;

[0080] For the polyvinyl alcohol coating, it can be dried at a temperature of 50℃-70℃ for 2-4 hours to allow the polyvinyl alcohol to fully form a film;

[0081] For the polydopamine coating, it can be dried at room temperature for 12-24 hours to allow the polydopamine coating to stably adhere to the substrate layer;

[0082] S5, preparing a colloid base solution;

[0083] Prepare the appropriate solution based on the type of glial substrate selected;

[0084] If it is gum arabic, add gum arabic powder to an appropriate amount of water, heat to 50°C-60°C and stir to dissolve it to form a solution with a mass concentration of 10%-20%;

[0085] If it is gelatin, soak the gelatin particles in warm water for a period of time and then heat to 40℃-50℃ to completely dissolve them to form a solution with a mass concentration of 8%-15%;

[0086] For polyvinyl butyral, dissolve it in an organic solvent, such as ethanol, to form a solution with a mass concentration of 15%-25%;

[0087] S6, coating the colloid base;

[0088] The prepared colloid base solution is evenly coated on the bottom of the substrate layer.

[0089] The spraying method can be used to ensure that the base solution is evenly covered on the bottom of the substrate layer, and the thickness can be controlled between 0.05 mm and 0.5 mm;

[0090] S7, drying and curing;

[0091] The paper coated with the colloid substrate is placed in the drying equipment again for drying and curing;

[0092] For gum arabic and gelatin bases, dry at 40℃-50℃ for 3-5 hours to fully solidify;

[0093] For the polyvinyl butyral substrate, it can be dried at 60°C-80°C for 2-3 hours to volatilize the organic solvent and solidify the substrate.

[0094] Furthermore, the hemp fiber contains more lignin and hemicellulose. For flax fiber, lignin degrading enzymes, such as laccase and xylanase, are used to decompose lignin and hemicellulose. Laccase can oxidize phenolic hydroxyl groups in lignin to make the lignin structure loose, while xylanase can hydrolyze xylan in hemicellulose. At a temperature of 40-50° C. and a pH of 4.5-5.5, the hemp fiber is immersed in an enzyme-containing buffer solution for 4-6 hours, which can effectively remove part of the lignin and hemicellulose without damaging the strength of cellulose. When the hemp fiber is made into paper, it can be better dispersed, thereby improving the uniformity and strength of the paper.

[0095] Furthermore, the main components of the straw fiber are cellulose, hemicellulose and lignin. For the straw fiber, dilute sulfuric acid treatment can be used. The straw fiber is immersed in a sulfuric acid solution with a mass fraction of 1-3%, and treated at 60-70°C for 2-3 hours. Sulfuric acid can hydrolyze the glycosidic bonds in the hemicellulose and partially dissolve the hemicellulose. At the same time, it can also cause a certain degree of degradation of lignin, thereby making the fiber better dispersed. However, it is necessary to control the acid concentration and treatment time to avoid excessive degradation of cellulose.

[0096] In the table:

[0097]

[0098] 1. Advantages of substrate layer

[0099] The paper substrates in the prior art mostly rely on traditional single plant fibers, and the limitations on material selection have limited the improvement of paper performance. The present invention innovatively selects hemp fibers or straw fibers as the core components of the substrate layer, which innovates the basic structure of paper from the source. Hemp fibers inject tough skeletons into paper with their high strength and excellent toughness, while straw fibers give paper environmental vitality with their wide sources, affordable costs and green degradation characteristics. The two are exquisitely interwoven to form a stable and flexible network structure. When this structure is subjected to external forces, the fibers work synergistically to disperse stress, greatly improving the initial strength and dimensional stability of the paper, far exceeding traditional paper, laying a solid foundation for paper to carry complex functions and adapt to diverse environments, building a bridge between sustainable development and high-performance requirements, filling the gaps in traditional technology in substrate material selection optimization, and opening up an innovative path for paper substrates.

[0100] 2. Polymer coating breakthrough

[0101] Traditional paper coatings have narrow functions and rigid adjustments, making it difficult to meet the precise needs of modern multi-scenario scenarios. The polymer coating of the present invention focuses on polyvinyl alcohol coatings, which build a continuous and dense protective film on the surface of the substrate with excellent film-forming technology, greatly reducing the invasion channels of liquids and gases, and pushing the waterproof and barrier properties to new heights; its flexible nature allows the coating to remain intact when the paper is repeatedly bent and curled, ensuring the stability of the structure and function, and reshaping the durability boundary of the paper; the hydrophilicity and water retention given by the molecular chain hydroxyl groups become the intelligent humidity adjustment center of the paper, accurately balancing moisture in different humidity requirements, safeguarding product quality and artistic value, breaking through the limitations of traditional coatings from multiple dimensions, achieving a leap in paper surface performance, and opening a new era of functional customizable coatings, deeply empowering paper in packaging, art and other fields.

[0102] 3. Innovation of the glial basal layer

[0103] In the past, the colloid base layer had a single viscosity and weak adaptability, which could not match the complex application ecology of paper. The present invention is ingenious and introduces a multi-system of gum arabic, gelatin and polyvinyl butyral. Gum arabic is based on natural polysaccharides, has moderate viscosity and good solubility. In the fields of food labels and handmade art papers, it anchors paper with green and environmentally friendly viscosity to prevent displacement and shedding; gelatin is derived from the hydrolyzed essence of animal collagen, has strong biological affinity and excellent viscosity and film-forming properties. In key scenarios of medical packaging and biological testing strips, it creates a solid bond between paper and biological samples or products to protect biological safety; polyvinyl butyral uses the power of synthetic polymers, is water-resistant and corrosion-resistant, transparent and bright, and builds a lasting protective embankment for paper in harsh environments such as outdoor advertising and waterproof labels to resist wind and rain erosion and chemical erosion. It breaks the shackles of traditional colloid bottom applications by precisely blending the viscosity, activates the pasting potential of paper in various fields, and reshapes the bottom adhesion and protection paradigm of paper.

[0104] 4. Changes in fiber pretreatment

[0105] Traditional technology is extensive in pre-treating hemp and straw fibers, resulting in frequent impurity residues and fiber damage, which weakens the quality of paper. The present invention uses targeted treatment tactics of lignin degrading enzymes (laccase, xylanase) for hemp fibers. In the precise temperature control (40-50°C) and acid-base balance (4.5-5.5pH) range, enzyme molecules accurately break the defense line of lignin phenolic hydroxyl and hemicellulose glycosidic bonds, efficiently remove impurities without damaging the strength of cellulose, and the fiber dispersion and paper uniformity and strength soar; the straw fiber is subjected to a mild degradation strategy of dilute sulfuric acid, following the precise concentration (1-3%), temperature (60-70°C) and time (2-3 hours) criteria, accurately regulating the hydrolysis and degradation process, optimizing the fiber dispersion state, and preventing excessive cellulose loss. The present invention innovates in the dimension of fiber pre-treatment, and fundamentally solves traditional problems. It is the gold standard for precision fiber pre-treatment in high-quality paper manufacturing, comprehensively improving the starting point of paper performance, and rewriting the fiber processing rules for paper manufacturing.

[0106] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A high wet strength nano silk paper, comprising a substrate layer (1), characterized in that: The substrate layer (1) is hemp fiber or straw fiber, and the plant fibers are interwoven to form a basic network structure of paper; A polymer coating layer (2) is coated on the top of the substrate layer (1), and a gelatin base layer (3) is provided at the bottom of the substrate layer (1).

2. The high wet-strength nano-silk paper according to claim 1, characterized in that: The polymer coating (2) is a polyvinyl alcohol coating or a polyvinyl alcohol coating.

3. The high wet-strength nano-silk paper according to claim 1, characterized in that: The colloid base layer (3) is gum arabic, gelatin or polyvinyl butyral.

4. The high wet-strength nano-silk paper according to claim 1, characterized in that: The thickness of the polymer coating (2) can be adjusted within a certain range to meet the requirements of different application scenarios for paper performance, and the coating thickness ranges from 0.1 mm to 1 mm.

5. A method for producing high wet-strength nano-silk paper, characterized in that: The following steps are included: S1, performing fiber pretreatment on the substrate layer (1); S2, preparing a polymer coating (2) solution; According to the type of the selected polymer coating (2), prepare a corresponding coating solution; If it is a polyvinyl alcohol coating, add polyvinyl alcohol powder to an appropriate amount of water, heat it to 80℃-90℃ and stir it to completely dissolve it to form a polyvinyl alcohol solution with a mass concentration of 5%-15%. Some additives such as dispersants and defoamers can be added as needed to improve the stability of the solution and the coating performance; In the case of a polydopamine coating, dopamine hydrochloride is dissolved in a buffer solution, such as tris(hydroxymethyl)aminomethane hydrochloride buffer, at a concentration of 1 g / L to 3 g / L, and then a certain amount of an oxidant, such as ammonium persulfate, is added under stirring to initiate a self-polymerization reaction of dopamine to form a polydopamine solution; S3, applying a polymer coating (2); Laying the pretreated substrate layer (1) flat on a coating device, and uniformly coating the polymer coating solution on the substrate layer (1) using a suitable coating method; The doctor blade coating method can be used to control the coating thickness between 0.1 mm and 1 mm by adjusting the gap and pressure of the doctor blade; You can also use the roller coating method, select a suitable coating roller, control the speed and pressure of the roller, and ensure that the coating is uniform and the thickness meets the requirements; S4, drying the polymer coating (2); placing the paper coated with the polymer coating (2) into a drying device for drying to remove moisture from the coating; For the polyvinyl alcohol coating, it can be dried at a temperature of 50°C-70°C for 2-4 hours to allow the polyvinyl alcohol to fully form a film; For the polydopamine coating, the coating can be dried at room temperature for 12-24 hours to allow the polydopamine coating to stably adhere to the substrate layer; S5, preparing a colloid base solution; Prepare the appropriate solution based on the type of glial substrate selected; If it is gum arabic, add gum arabic powder to an appropriate amount of water, heat to 50°C-60°C and stir to dissolve it to form a solution with a mass concentration of 10%-20%; If it is gelatin, soak the gelatin particles in warm water for a period of time and then heat to 40℃-50℃ to completely dissolve them to form a solution with a mass concentration of 8%-15%; For polyvinyl butyral, dissolve it in an organic solvent, such as ethanol, to form a solution with a mass concentration of 15%-25%; S6, coating the colloid base; The prepared colloid base solution is evenly coated on the bottom of the substrate layer. The spraying method can be used to ensure that the base solution is evenly covered on the bottom of the substrate layer, and the thickness can be controlled between 0.05 mm and 0.5 mm; S7, drying and curing; The paper coated with the colloid substrate is placed in the drying equipment again for drying and curing; For gum arabic and gelatin bases, dry at 40℃-50℃ for 3-5 hours to fully solidify; For the polyvinyl butyral substrate, it can be dried at 60°C-80°C for 2-3 hours to volatilize the organic solvent and solidify the substrate.

6. The method for manufacturing high wet-strength nano-silk paper according to claim 5, characterized in that: The hemp fiber contains more lignin and hemicellulose. For the flax fiber, lignin degrading enzymes, such as laccase and xylanase, are used to decompose lignin and hemicellulose. Laccase can oxidize phenolic hydroxyl groups in lignin to make the lignin structure loose, while xylanase can hydrolyze xylan in hemicellulose. At a temperature of 40-50°C and a pH of 4.5-5.5, the hemp fiber is immersed in an enzyme-containing buffer solution for 4-6 hours, which can effectively remove part of the lignin and hemicellulose without damaging the strength of cellulose. When the hemp fiber is made into paper, it can be better dispersed, thereby improving the uniformity and strength of the paper.

7. The method for manufacturing high wet-strength nano-silk paper according to claim 5, characterized in that: The main components of the straw fiber are cellulose, hemicellulose and lignin. For the straw fiber, dilute sulfuric acid can be used for treatment. The straw fiber is immersed in a sulfuric acid solution with a mass fraction of 1-3%, and treated at 60-70°C for 2-3 hours. Sulfuric acid can hydrolyze the glycosidic bonds in the hemicellulose and partially dissolve the hemicellulose. At the same time, it can also cause a certain degree of degradation of lignin, thereby making the fiber better dispersed. However, it is necessary to control the acid concentration and treatment time to avoid excessive degradation of cellulose.